PELATIHAN AAS UNTUK PENINGKATAN KETRAMPILAN SISWA SMK KADIRI KRAS - Rachma Agustina; Dwi Ari Pertiwi; Meta Ardiana, (Prosiding Seminar Nasional Sains, Teknologi, Ekonomi, Pendidikan dan Keagamaan (SAINSTEKNOPAK), 2021)
The purpose of this community service is to improve student skills through basic accounting computer training based on accurate accounting software. The development of technology is so fast and also the demands of the business world that must present financial reports quickly, reliably and accurately, so this condition encourages accounting students to have good knowledge of this application to be able to increase their skills. The training was carried out in two waves, starting with the creation of a company database and then continuing with hands-on practice using this application for the case of service and trading companies. Sharing discussion with the presenters was carried out by the participants enthusiastically. The results of this community service program can increase the knowledge and skills of the trainees.